TANGGUNG JAWAB EMITEN DAN PROFESI PENUNJANG ATAS ADANYA PROSPEKTUS YANG TIDAK BENAR DALAM KEGIATAN DI PASAR MODAL - Andi Wijaya, I Kadek; Sukeni, Ni Nyoman (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 08, September 2013, 2013)
The title of this legal research is the responsibility of the issuer and the professions on the prospectus which is not true in the activities in the capital market. The capital market is a meeting place of demand and supply of capital. Parties who offer investors and the capital is in need of capital is the issuer. In capital market activities known as the principle of transparency (disclosure), the entire disclosure of accurate information about the state of the business carried on issuers to the general public, especially to investors. To embody the principle of transparency in the capital market public companies supporting professionals who assisted the prospectus must provide written information in connection with a public offering. In the capital market issuers often do not disclose information about the true state of his own efforts. The purpose of this study was to determine the responsibility of the issuer of the prospectus and supporting professionals who do not know the correct and legal consequences for the issuer and the parties associated with the manufacture of a prospectus which is not true. Types of research used in this paper is the normative legal research. Collection techniques used were legal materials library research (library research). This type of approach is the approach used legislation. Conclusions from this research is the responsibility of the issuer and the professions on the prospectus which is not true in the capital market is the obligation of the issuer and supporting professionals to legally liable to pay compensation to investors for losses suffered as a result of which the prospectus is not the right. Legal sanctions for issuers and related professions in making prospectus is administrative sanctions, criminal sanctions, civil sanctions.
Keywords: Issuers, Disclosure Principle, Prospectus, Supporting Professional